Mindful Parenting and Depression in Working Mothers - Kurnianda, Muhammad; Rinaldi, Martaria Rizky (Universitas Negeri Semarang, 2025)
Depression is a significant mental health issue among working mothers, which can negatively impact their quality of life and family well-being. One potential approach to mitigating the risk of depression is mindful parenting, which involves paying full attention and awareness to the present moment in interactions with children. This research investigates the association between the practice of mindful parenting and the prevalence of depressive symptoms among employed mothers. This research employs a quantitative correlational approach, involving 100 working mothers selected through convenience sampling. Data were collected using the Mindful Parenting Scale and the Beck Depression Inventory-II (BDI-II), and analyzed using Spearman's correlation test. The results indicate a significant negative relationship between mindful parenting and depression (r = -0,317, p = 0,001). This finding suggests that higher levels of mindful parenting are associated with lower levels of depression in working mothers. Conversely, lower levels of mindful parenting are associated with higher levels of depression. The study's conclusion posits that mindful parenting may act as a buffer, mitigating the risk of depression for working mothers. Based on these findings, it is recommended to develop and implement mindfulness and mindful parenting training programs as part of mental health support for working mothers.